1989
DOI: 10.1620/tjem.157.199
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological features of vascular responses of isolated rat common carotid arteries to vasroactive substances revealed by the cannula insering method.

Abstract: Using the cannula inserting method, we studied vascular responses of isolated rat common carotid arteries to 15 vasoactive substances. Intraluminal injections of phenylephrine, norepinephrine (NE), angiotensin II, 5-hydroxytryptamine (5-HT) and prostaglandin FZa (PGFZa) induced a strong vasoconstriction in such a way that a maximum increase in perfusion pressure amounted to approximately 50 mmHg. The order of their potencies were as follows : Phenylephrine >_ NE _> angiotensin II > PGFZa >_ 5-HT>>KCI. The sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1990
1990
2007
2007

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…We found that a bolus administration of noradrenaline and phenylephrine caused a long-lasting vasoconstrictor response (1). In the present study, we examined effects of three different a1-adrenoceptor agonists, noradrenaline, phenylephrine and methoxamine.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…We found that a bolus administration of noradrenaline and phenylephrine caused a long-lasting vasoconstrictor response (1). In the present study, we examined effects of three different a1-adrenoceptor agonists, noradrenaline, phenylephrine and methoxamine.…”
Section: Discussionmentioning
confidence: 84%
“…In the past we studied the functional characteristics of vascular responses of isolated rat common carotid arteries (1,7,8). We found that a bolus administration of noradrenaline and phenylephrine caused a long-lasting vasoconstrictor response (1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cumulative dose–response curves for the receptor agonists phenylephrine (PE) (1 × 10 −9 to 1 × 10 −5 mol/L), prostaglandin F 2α (PGF 2α ) (1 × 10 −9 to 1 × 10 −5 mol/L) and serotonin (5HT) (1 × 10 −9 to 1 × 10 −5 mol/L) were then recorded for each arterial ring. These three agonists are all potent constrictors of the rat carotid artery (10). A receptor agonist applied to SMC couples with its receptors on the cellular membrane and activates the G‐proteins.…”
Section: Methodsmentioning
confidence: 99%